REVIEW OF CRIMINAL LAW ON MANIPULATION OF PT ASABRI'S FINANCIAL STATEMENTS AS AN ACT OF FRAUD - Ratu Frisya Ritonga; Adlin Budhiawan (Warmadewa Press, 2024)
Fraud is an act that violates the law and can cause harm to many parties. Literally, fraud is a term that comes from the English language which means fraud. Fraud can also be interpreted as an unlawful act that is carried out intentionally, such as manipulation or providing false reports to other parties to obtain personal or group gain. This act can be a falsification of financial statements that are manipulated intentionally to gain personal gain. The research conducted by the author aims to examine the review of criminal law on the manipulation of financial statements as an act of fraud in one of the cases that is quite excited about manipulation and state losses in Indonesia, namely PT. ASABRI Social Insurance for the Armed Forces of the Republic (Persero). This research uses normative research through a concept approach, case approach and statutory approach (statue approach). The nature of the research is analyzed using descriptive research, data collection methods in the form of literature studies, and the data obtained will be analyzed using inductive analysis methods. The results of this study indicate that the case of PT Asabri (Persero) is a case that has a relationship to fraud that is proven by violations or manipulation of financial statements that occurred at PT Asabri and the resolution of this case is dominated by settlement through the legal process of corruption based on Article 2 (1) and article 3 of Law No.31 of 1999 concerning Eradication of Corruption which was amended by Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning Eradication of Corruption. The conclusion in this case is that the case of PT Asabri (Persero) is fraud with the category of corruption schemes and manipulation of financial statements.